Possible underdiagnosis of ulcerative colitis in tertiary care can affect medication use and access to healthcare facilities - Ferraro, Sara; Bartolini, Claudia; Convertino, Irma; Bertani, Lorenzo; Costa, Francesco; Cappello, Emiliano; Paoletti, Olga; Giometto, Sabrina; Gini, Rosa; Lucenteforte, Ersilia; Tuccori, Marco (Frontiers in Immunology, 2026)
BackgroundUlcerative colitis (UC) is a chronic inflammatory bowel disease where diagnostic delays can worsen the clinical outcomes and increase the strain on healthcare systems. This study investigated the frequency of potentially missed UC diagnoses in tertiary care and their impact on treatment patterns and healthcare utilization.MethodsWe conducted a retrospective cohort study using Tuscany’s regional healthcare database (2006–2020). Adults newly diagnosed with UC between 2011 and 2018 were included. A “possible missed diagnosis” was defined as a hospital or emergency department (ED) visit for gastrointestinal (GI) symptoms occurring 7–60 months before the UC diagnosis. We assessed the initiation of azathioprine and non-conventional therapies, as well as the rates of ED visits, hospital admissions, and surgery. Survival analyses and Cox regression models were applied.ResultsAmong 3,804 patients with UC, 313 (8.3%) had prior GI-related tertiary care visits suggestive of a missed diagnosis. The mean time to diagnosis was 27.5 months. Compared with those who were timely diagnosed, these patients were not more likely to start azathioprine or non-conventional therapies. However, subjects with a possible missed diagnosis had higher rates of ED visits [adjusted hazard ratio (aHR) = 1.8, 95%CI = 1.5–2.0], hospitalizations (aHR = 1.4, 95%CI = 1.2–1.7), and combined urgent care encounters (aHR = 1.5, 95%CI = 1.3–1.7) compared with other patients.ConclusionsPatients with a potentially missed UC diagnosis are more likely to need emergency and inpatient care, despite receiving similar treatments. Promoting earlier recognition of UC symptoms in tertiary care may reduce avoidable hospital use and improve disease management.